Church, state and civil society - Fergusson, David (Cambridge University Press, 2004)
This book revisits the tradition of Christian political theology and explores the relationship of the church to the state and civil institutions via the concept of civil society. It assesses the effect of the First Amendment in the USA and defends the case for continuing disestablishment in England and Scotland.